Animal heroes :True Stories of Extraordinary Creatures - Holt, Ben (Crows Nest Allen & Unwin, 2015)
The most extraordinary true tales of bravery across the natural world, from domestic pets to wild animals, proving that when it comes to facing danger there's more to them than meets the eye.
Including Illustration
Keywords: Animal heroes -- Animal behavior -- Animals